Do Smoking and Socioeconomic Factors Influence Imaging Outcomes in Axial Spondyloarthritis? Five-Year Data From the DESIR Cohort - Nikiphorou, Elena (2020)
Objective: To investigate the relationship between smoking and imaging outcomes over 5 years in axial spondyloarthritis (SpA) and to assess whether socioeconomic factors influence these relationships. Methods: Axial SpA patients from the Devenir des Spondylarthropathies Indifferérenciées Récentes cohort were included. The following 4 imaging outcomes were assessed by 3 central readers at baseline, 2 years, and 5 years: spine radiographs (using the modified Stoke Ankylosing Spondylitis Spine Score [mSASSS]), sacroiliac (SI) joint radiographs (using the modified New York criteria), magnetic resonance imaging (MRI) of the spine (using the Spondyloarthritis Research Consortium of Canada [SPARCC] score), and MRI of the SI joint (using the SPARCC score). The explanatory variable of interest was smoking status at baseline. Interactions between smoking and socioeconomic factors (i.e., job type [blue-collar or manual work versus white-collar or nonmanual work] and education [low versus high]) were first tested, and if significant, analyses were run using separate strata. Generalized estimating equations models were used, with adjustments for confounders. Results: In total, 406 axial SpA patients were included (52% male, 40% smokers, and 18% blue collar). Smoking was independently associated with more MRI-detected SI joint inflammation at each visit over the 5 years, an effect that was seen only in patients with blue-collar professions (β = 5.41 [95% confidence interval (95% CI) 1.35, 9.48]) and in patients with low education levels (β = 2.65 [95% CI 0.42,4.88]), using separate models. Smoking was also significantly associated with spinal inflammation (β = 1.69 [95% CI 0.45, 2.93]) and SI joint damage (β = 0.57 [95% CI 0.18, 0.96]) across all patients, irrespective of socioeconomic factors and other potential confounders. Conclusion: Strong associations were found between smoking at baseline and MRI-detected SI joint inflammation at each visit over a time period of 5 years in axial SpA patients with a blue-collar job or low education level. These findings suggest a possible role for mechanical stress amplifying the effect of smoking on axial inflammation in axial SpA.